Exploring the potential of sago residue for eco-friendly construction materials - Imran, Al Ichlas; Siregar, Januar Parlaungan; Palanisamy, Sivasubramanian; Cionita, Tezara; Deni Fajar Fitriyana, .; Rozanna Dewi, .; Laksmono, Joddy Arya; Roseno, Seto; Mausam, Kuwar; Sankar, Subramanian Lakshmi; Massoud, Ehab El Sayed; Al-Farraj, Saleh A. (North Carolina State University, 2025)
Sago residue is being explored as an alternative material in construction materials because of its natural source, good performance, eco-friendly nature, and biodegradable properties. Sago residue is categorized into particles and fiber, so it has various fabrication methods and applications. This study examines various sago residue extraction methods, including traditional manual techniques, mechanical processes, and chemical or enzymatic methods, highlighting their impact on the properties of construction materials. Furthermore, factors such as constituent materials, processing methods, composition, fiber and particle size, environmental conditions, and manufacturing processes can all influence the physical and mechanical properties of sago residue-based construction materials. This review emphasizes the importance of material characterization in understanding their suitability for specific construction applications, ensuring product quality and safety, and identifying opportunities for sustainable development in the construction industry. It was also shown that this study provides important insights and explores the potential of sago waste as a construction material that can be degraded in the environment. Future research may explore the impact of fiber and fiber orientation treatments on the heat resistance, sound absorption ability, and tribology properties of construction materials made from sago waste.